2011
DOI: 10.1007/s00217-011-1453-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of modified atmosphere packaging (MAP) with low and superatmospheric oxygen on the quality and antioxidant enzyme system of golden needle mushrooms (Flammulina velutipes) during postharvest storage

Abstract: To quantify the eVect of oxygen concentrations on the quality and antioxidant enzyme system of stored golden needle mushroom, modiWed atmosphere packaging (MAP) with low and initial superatmospheric oxygen was applied during mushroom storage, and physiological changes associated with postharvest deterioration, activities of antioxidant enzymes, and of cellulase, were monitored during subsequent storage for 0-34 days. Golden needle mushrooms stored in MAP without oxygen or 20-50% oxygen rate had a poorer sensor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 33 publications
0
19
0
1
Order By: Relevance
“…Similar results were reported in heat‐treated sliced mushrooms, in which higher SOD and CAT activity was accompanied by lower browning (Zhang et al, ). The changes of SOD and CAT resulted from HT may be owing to the changes of antioxidant enzymes‐related gene expression, which led to an increased antioxidant protective response to abiotic stress (Wang et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Similar results were reported in heat‐treated sliced mushrooms, in which higher SOD and CAT activity was accompanied by lower browning (Zhang et al, ). The changes of SOD and CAT resulted from HT may be owing to the changes of antioxidant enzymes‐related gene expression, which led to an increased antioxidant protective response to abiotic stress (Wang et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…The firmness decrease in mushrooms was reported to be partially due to the increased activity of endogenous autolysins . Wang et al . found that cellulase could degrade mushroom tissue and decrease its firmness.…”
Section: Resultsmentioning
confidence: 99%
“…The extraction and determination of Polyphenol oxidase (PPO) were adapted from the method described by Wang et al. (2011).…”
Section: Methodsmentioning
confidence: 99%